Survey of Canadian Kidney Transplant Specialists on the Management of Morbid Obesity and the Transplant Waiting List. Issue 1 (29th November 2016) - Chan, Gabriel; Soucisse, Mikael
Background: Obesity is associated with increased surgical complications and long-term cardiovascular mortality. Studies of access in kidney transplantation have found a bias against obese patients on the wait-listing. Objective: To determine the current state of clinical practice for the management of obesity in kidney transplantation. Design: A survey in two versions, PDF and traditional paper, composed of categorical questions. Setting: A pan-Canadian survey of transplant nephrologists and surgeons. Methods: The survey PDF was distributed electronically to the Kidney Group of the Canadian Society of Transplantation. A shorter, hardcopy version was distributed subsequently at a national transplant meeting. Results: There were 47 responses, including almost every Canadian adult transplant program. Most (81%) reported the use of a body mass index limit for access to the waiting list. However, only 40% reported a strict enforcement. There were several instances of intra-hospital disagreements regarding the use of a policy, among the centers with multiple responses. The body mass index limit was most commonly 40 kg/m 2 (62%), followed by 35 kg/m 2 (36%). Despite the body mass index limit, few centers (30%) reported having a weight management program. The reported experience with bariatric surgery was small, though nearly all replied that they would refer to a bariatric specialist in the future. Limitations: This national survey provides a broad assessment of clinical practice. The distinction between an official policy and informal clinical tendencies is difficult. The results cannot be used to support any specific limit or policy. Conclusions: This survey found that the body mass index limit for access to the kidney transplant waiting list was common in Canada. Several inconsistencies suggest a lack of official policy. To achieve equity in access, clear guidelines for obesity should be established and enforced. Bariatric surgery has the promise of rapid weight loss. Resource allocation to study obesity in transplant patients will be essential.